2017
DOI: 10.1007/s40430-017-0750-8
|View full text |Cite
|
Sign up to set email alerts
|

A two-way FSI analysis of multiphase flow in hydrodynamic journal bearing with cavitation

Abstract: Abbreviations e Eccentricity between shaft and bearing, m C Radial clearance, m R Radius of the shaft, m h Film thickness, m ω Angular velocity, rad/sec W Load carrying capacity, N O' Bearing centre O Shaft centre ρ Fluid density, kg/m 3 ρ l Liquid density, kg/m 3 ρ v Vapor density, (kg/m 3) v Fluid velocity P Static pressure, Pa τ Stress tensor F External body force, N t Time ε Eccentricity ratio σ Liquid surface tension coefficient v Fluid velocity vector C e , C c Mass transfer source terms connected to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
(26 reference statements)
2
23
0
Order By: Relevance
“…In the above equation, P cav is the pressure in the cavitation region, = cav is the mass fraction (dimensionless density) of the lubricant film, and g is the switch function, and makes it possible to solve one single equation (modified Reynolds equation) for both the full film and the oil whip regions. The value of the function g in the region of the full film is equal to 1, and in the oil whip region, it is equal to zero [20]. It could be shown that the modified form of the Reynolds equation 7is achievable in the following form, taking into account the compressibility effects due to the cavitation [Eq.…”
Section: Fig 1 Simple Schematic Of the Journal Bearing Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…In the above equation, P cav is the pressure in the cavitation region, = cav is the mass fraction (dimensionless density) of the lubricant film, and g is the switch function, and makes it possible to solve one single equation (modified Reynolds equation) for both the full film and the oil whip regions. The value of the function g in the region of the full film is equal to 1, and in the oil whip region, it is equal to zero [20]. It could be shown that the modified form of the Reynolds equation 7is achievable in the following form, taking into account the compressibility effects due to the cavitation [Eq.…”
Section: Fig 1 Simple Schematic Of the Journal Bearing Geometrymentioning
confidence: 99%
“…Dhande and Pande [20] utilized the structured hexahedral and unstructured tetrahedral meshes to discretize fluid domain and solid domain (journal bearing), respectively, and achieved the very accurate pressure distribution in the hydrodynamic journal bearing by solving the Navier-Stokes equations. However, in the present research, the model is based on the two-dimensional Reynolds equation (9) described in Sect.…”
Section: Numerical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the CFD-FSI methodology, Wang et al 6 found that elastic deformation increased with increasing rotating speed and decreasing Poisson's ratio for the water-lubricated journal bearing. Dhande and Pande 7 proposed that the peak pressure was decreased due to cavitation effect when elastic deformation was considered. Lin et al 8 used also the CFD-FSI approach to study effects of recess configuration on lubricating properties, and their work revealed that ladder-type recess could help journal bearings inhibit oil temperature rise and cavitation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need to develop an easy and user-friendly method for three lobe bearing analysis. The method described in detail by Dhande and Pande [3,4] is used here for analysing three lobe bearing. The method is based on computation of hydrodynamic fluid forces using computational fluid dynamics (CFD) and the bearing shell deformations using finite element structural module.…”
Section: Introductionmentioning
confidence: 99%